Multilateral Use of Dandelion in Folk Medicine of Central-Eastern Europe - Robert Gruszecki; Magdalena Walasek-Janusz; Gianluca Caruso; Robert Pokluda; Alessio Vincenzo Tallarita; Nadezhda Golubkina; Agnieszka Sękara (Plants)
Background: Dandelion (Taraxacum sect. Taraxacum, also referred to as Taraxacum officinale F.H. Wiggers coll.), a collective species of perennial herbaceous plants of the Asteraceae family, is commonly considered weed; however, in the traditional societies of Central-Eastern Europe, it is a source of food and medicinal raw materials. The growing interest in the medicinal properties of herbal raw materials of dandelion encouraged us to focus on their use in the traditional folk medicine of Central-Eastern European communities. Aim: The hypothesis of the present study suggests that Taraxacum sect. Taraxacum (dandelion), which is widespread throughout Central-Eastern Europe and easily identifiable, has had notable applications in ethnopharmacology. The study aims to examine the medicinal properties of this species, focusing on its traditional uses in folk medicine across the region. The resulting data may serve as a valuable resource for contemporary pharmacognosy research. Methods: The analysis was based on publications dated from the end of the 18th century to the beginning of the 21st century, mainly from Poland. In addition, the study includes publications on contemporary Belarus, Ukraine, and European Russia. Results: The research showed that dandelion provided many medicinal raw materials, but the available literature did not mention the use of the herb’s root, a raw material popular in contemporary natural medicine. During the period analysed, an increase in the types of raw materials was observed, and the order in which they appeared in the sources was as follows: latex > root = leaf = inflorescence > herb > herb with flowers. Additionally, a review of the literature indicated that the number of conditions under which they were used increased during the investigation period. The variety of ways to prepare the raw material is noteworthy; fresh and dried raw materials were used to make extracts, tinctures, decoctions, infusions, wrap compresses, syrups, and even wine or coffee substitutes. The mentioned preparations were prepared individually for particular ailments. Conclusions: The vast experience of rural communities in Central-Eastern Europe concerning the medicinal applications of common dandelion has developed through centuries. The experience of rural communities may influence the direction of further phytochemical and pharmacological research.